Marine and terrestrial biostimulant elicitors of tolerance to cold stress - Oliveira, Eva Regina; Nunes, Aline; Dutra, Felipe de Souza; Azevedo, Gadiel Zilto; Schneider, Alex Ricardo; Santos, Beatriz Rocha dos; Munaro, Deise; Moura, Sidnei; Lima, Giuseppina Pace Pereira; Maraschin, Marcelo (Frontiers in Plant Science, 2025)
The increasing frequency of adverse environmental events, driven by ongoing climate change, has intensified the search for new technological alternatives in crop production and plant protection. Thermal stress can limit plant adaptation and negatively impact metabolism, physiology, morphology, and yield. Cold stress in plants has been extensively studied and can affect various stages of plant’s life cycle, from seed formation to development, causing damage to cell membranes, impairing cell division, and disrupting water absorption. Consequently, researchers have focused on mitigating the impacts of abiotic stress by investigating bioactive molecules and biostimulants derived from various organisms, which enhance tolerance mechanisms in plants. In aquatic environments, macro- and microalgae have emerged as key sources of plant elicitors, providing extractable molecules such as polysaccharides, polyamines, polyphenols, and amino acids that enhance plant defense responses. Similarly, certain terrestrial plants have shown potential as sources of biostimulant compounds. Thus, this study aims to highlight advancements in crop systems by emphasizing the potential of algae-based and terrestrial biostimulant elicitors in enhancing tolerance to cold stress. Ultimately, the goal is to improve understanding of promising biological models for food production, fostering innovative developments that can contribute to economically and ecologically sustainable technologies.